Desiccation and Cryopreservation of Embryonic Axes of Hevea brasiliensis Muell. - Arg. - M. N., Normah; Chin, H. F.; Hor, Yue Luan (1986)
Hevea embryonic axes were desiccated for a period of 1 - 5 hours and the moisture content was determined at the end of each hour of desiccation. Another set of embryonic axes were aseptically desiccated for the same period before they were cryopreserved for 16 hours by direct immersion in liquid nitrogen (-196°C). At a moisture content between 14 - 20% (desiccation for 2 - 5 hours), 20 - 69% of the embryonic axes survived cryopreservation and formed seedlings with normal roots and shoots when cultured in vitro. A bnormalities were deteched in some seedlings however, hence, refinement of the technique is needed.